Beyond display and referential questions: Teacher questioning as contingent scaffolding in Indonesian EFL reading instruction - Masduki Masduki; Anton Haryadi; Dadang Zakaria (Universitas Islam Negeri Ar-Raniry, 2026)
Teacher questioning plays a pivotal role in shaping classroom interaction and fostering cognitive engagement in English as a Foreign Language (EFL) context. This qualitative multiple-case study investigates how Indonesian university EFL instructors employ questioning practices in reading comprehension courses, focusing on question types, interactional strategies, and their influence on student responses. Grounded in cognitive engagement theory and classroom discourse analysis, data were collected through non-participant classroom observations, audio-visual recordings, field notes, and semi-structured interviews with two instructors at the Language Center of Universitas Muhammadiyah Malang. A total of 412 question–response units were analyzed using thematic coding and descriptive frequency analysis. The findings reveal a predominance of display questions, whereas referential and procedural questions occurred less frequently. However, referential and probing questions generated longer, more inferential, and cognitively elaborated student responses. Translation, repetition, and strategic pausing emerged as core scaffolding strategies that mediated comprehension and participation. The study demonstrates that effective questioning resides not merely in the proportion of display versus referential questions, but rather in their strategic sequencing and adaptive modification according to learners' proficiency levels and classroom dynamics. By highlighting the dialogic and scaffolding functions of teacher questioning, this research contributes to classroom discourse scholarship and offers practical implications for fostering balanced, cognitively engaging reading instruction in EFL higher education contexts.